The Truth about Carpal Tunnel Syndrome: Finding Answers, Getting Well - Gambaro, Jill (Rowman & Littlefield Publishers, 2014)
It can start in any number of ways: A legal secretary notices a strange buzzing in her palm. It soon spreads to a fiery ache across her entire upper body. Within a few months, she becomes totally disabled. Trapped in the medical and legal systems without any answers, she desperately attempts to regain her health and her livelihood. Fifteen percent of Americans suffer from pain associated with Carpal Tunnel Syndrome, but only 5 percent ever receive that diagnosis. Medical science does not agree on what causes it or even if it exists. Technology has caused incidents to skyrocket, making nearly everyone susceptible—even teenagers and children. It is the number one occupational illness in the United States, and the most common cause of physical disability in the world, costing approximately $850 billion a year in this country alone. The Truth About Carpal Tunnel Syndrome is a compelling patient account of this controversial injury. Using layman’s terms, the book describes why it’s so difficult to treat, how the author learned to manage hers, and how the medical and legal systems work in conflict to those suffering such injuries. Offering hope to sufferers and their loved ones, this book captures the reality of carpal tunnel syndrome and suggests ways for dealing not just with the injury but with the systems in place to deal with the losses associated with carpal tunnel syndrome.